Oil of Gladness and the Immortal High Priest in Hebrews - Duff, Justin Harrison (The journal of theological studies, 2023)
The anointment of Jesus with the ‘oil of gladness’ in Hebrews 1 is a puzzling feature of Hebrews’ argument. The anointment—which is drawn from Psalm 45 and connected to Christ’s messianic enthronement—is often regarded as a royal investiture that transpired after the death of Christ. The relationship with royal messianism and heavenly enthronement, however, may overshadow another significant function of the oil of gladness: high priestly consecration and bodily immortalization. In this article, the function of Christ’s anointment is explored against uses of Psalm 45 in early Judaism and Greco-Roman and Second Temple traditions that depict heavenly oil as an agent of bodily transformation. These traditions suggest that Jesus’ anointment in Hebrews may signify a priestly consecration that transforms and immortalizes the human body for the heavenly realms. The anointment of Jesus in Hebrews may therefore be connected to the incarnate Son’s inheritance of ‘indestructible life’ (7:16) and clarifies when Jesus ‘became’ a royal-priestly Messiah ‘for the ages’.